Analisis Pengaruh Insentif Dan Budaya Organisasi Terhadap Kinerja Karyawan Dengan Komitmen Organisasi Sebagai Variabel Mediasi (Studi Lembaga Amil Zakat (LAZ) Kota Semarang) - Edy Suhendro (International Forum of Researchers and Lecturers, 2023)
The purpose of this study was to analyze the effect of incentives and organizational culture on employee performance and organizational commitment as a mediating variable in Semarang amil zakat institutions. The population of this study is 265 people and the samples taken as many as 159 people. The data analysis used is path analysis (Path) multiple regression model.The analysis showed that: H1 Incentive positive effect on organizational commitment, H2 Organizational culture positively affects organizational commitment, H3 Komiten organization positive effect on performance, H4 Incentives positive effect on performance, H5 organizational culture brpengaruh positively to performance, H6 organizational commitment can mediate incentives for performance, organizational commitment H7 can mediate organizational culture on performance.